POLYSEMY FROM THE PERSPECTIVE OF THE SCIENTIFIC STUDY OF TERMINOLOGY (TAMADDUN NURI JURNALI, 2024)
This article deals with the discussion of polysemy, the definition of the word, and a few" words "about the idea of "word" because it is crucial to understand what a word actually means and the first comprehending of the "word," the basic linguistic unit that unites meaning and form, it is impossible to talk about the function of meaning.